2021
DOI: 10.1097/shk.0000000000001894
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Interaction of TREM-1 and eCIRP Attenuates Inflammation and Improves Survival in Hepatic Ischemia/Reperfusion

Abstract: Introduction: Triggering receptor expressed on myeloid cells-1 (TREM-1) has important implications in sepsis and inflammation and is a novel receptor for extracellular cold-inducible RNA-binding protein (eCIRP). We hypothesize that the inhibition of TREM-1 via its interaction with eCIRP by novel peptide inhibitor M3 or knockout gene will attenuate the inflammation and injury associated with severe hepatic ischemia/reperfusion (I/R). Methods: Wild-type (WT) C57BL/6 and TREM-1 -/mice underwent 60 min of 70% hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 44 publications
0
29
0
1
Order By: Relevance
“…In lung fibroblasts, eCIRP amplifies pro-inflammatory cytokines in a TLR4-dependent manner, triggering pulmonary fibrosis ( 54 ). As a receptor for eCIRP, TREM-1 plays a vital role in ischemia-reperfusion in the liver, intestine, and other organs ( 60 ), and induces inflammation in macrophages and neutrophils ( 35 ), forming NETs ( 61 ). In hemorrhagic shock and sepsis, TREM-1 can also be a key target of eCIRP ( 16 , 56 , 62 ).…”
Section: Role Of Ecirp In Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung fibroblasts, eCIRP amplifies pro-inflammatory cytokines in a TLR4-dependent manner, triggering pulmonary fibrosis ( 54 ). As a receptor for eCIRP, TREM-1 plays a vital role in ischemia-reperfusion in the liver, intestine, and other organs ( 60 ), and induces inflammation in macrophages and neutrophils ( 35 ), forming NETs ( 61 ). In hemorrhagic shock and sepsis, TREM-1 can also be a key target of eCIRP ( 16 , 56 , 62 ).…”
Section: Role Of Ecirp In Inflammatory Diseasesmentioning
confidence: 99%
“…During hepatic I/R, the binding of eCIRP to TREM-1 increases the number of inflammatory cells in the liver leading to increased tissue damage therein. M3 treatment, on the other hand, had an increased effect on the survival rate of mice after hepatic I/R ( 60 ). When M3 competes with TREM-1, it also blocks the eCIRP signaling pathway in the heart ( 80 ) and kidney ( 81 ).…”
Section: Inhibitors Of Cirpmentioning
confidence: 99%
“…Extracellular cold-inducible RNA-binding protein levels started to increase by 4 hours after hepatic I/R and significantly increased from baseline at 24 hours later. The protective effects of an anti-CIRP antibody and TREM-1 inhibition via peptide inhibitor have been shown in hepatic I/R 8,11 . Therefore, eCIRP released into circulation as early as 4 hours after hepatic I/R could bind to exogenous PS-OMe miR130 and has the potential to prevent hepatic I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also synthesized a novel peptide inhibitor, M3, that could block the interaction between eCIRP and TREM-1 and inhibit the eCIRP-mediated inflammatory response. Borjas et al [ 67 ]. used M3 to treat hepatic ischemia/reperfusion (I/R) mice and found that M3 attenuated hepatic I/R injury by inhibiting TREM-1.…”
Section: Trem-1 Ligandsmentioning
confidence: 99%